Fluoride retention in saliva and in dental biofilm after different home-use fluoride treatments - Daniela Correia Cavalcante SOUZA; Marisa MALTZ; Lina Naomi HASHIZUME (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This single-blind, randomized, crossover study aimed at assessing the long-term fluoride concentrations in saliva and in dental biofilm after different home-use fluoride treatments. The study volunteers (n = 38) were residents of an area with fluoridated drinking water. They were administered four treatments, each of which lasted for one week: twice-daily placebo dentifrice, twice-daily fluoride dentifrice, twice-daily fluoride dentifrice and once-daily fluoride mouthrinse, and thrice-daily fluoride dentifrice. At the end of each treatment period, samples of unstimulated saliva and dental biofilm were collected 8 h after the last oral hygiene procedure. Fluoride concentrations in saliva and dental biofilm were analyzed using a specific electrode. The fluoride concentrations in saliva and dental biofilm 8 h after the last use of fluoride products did not differ among treatments. The results of this study suggest that treatments with home-use fluoride products have no long-term effect on fluoride concentrations in saliva and in dental biofilm of residents of an area with a fluoridated water supply.